A confirmatory analysis of the individual entrepreneurial orientation scale [Un anÁlisis confirmatorio de la escala individual entrepreneurial orientation] (2020)
In this article the Individual Entrepreneurial Orientation scale was adapted. This scale has not been validated in any other language, so the aim was to analyze the psychometric properties of the Spanish version. After exploratory factor analysis, the first sample confirmed a unifactorial 10-item solution. Results of confirmatory factor analysis in a second sample were rmsea = .05, cfi = .95, and tli = .95, replicating the exploratory results while maintaining the same number of items. The resulting dimension showed good reliability (.73 and .80). Subsequently, the scale scores related to several external correlates and other scales, exhibiting good convergence and criterion validity. These indicate that the scale is a reliable and valid instrument, and its Spanish adaptation is suitable. © 2020 Sociedad Mexicana de Psicologia. All rights reserved.